A Proposal on Neurological Dose–Response Relationship for Inclusion in ISO 5349-1 Documentation to be Used in Tropical Environment - Su, Anselmting; Maeda, Setsuo; Fukumoto, Jin; Miyai, Nobuyuki; Takemura, Shigeki; Bulgiba, Awang Mahmud; Yoshimasu, Kouichi; Miyashita, Kazuhisa (Springer Singapore, 2016)
The objective of this paper is to calculate the association between the eight-hour time weighted average vibration exposure, A(8) and years of vibration exposure in the tropical environment using the results of hand-arm vibration syndrome (HAVS) study conducted among a total of 173 male construction, forestry, and automobile manufacturing plant workers in Malaysia. We found that the relationship between A(8) and years of vibration exposure for neurological symptoms in tropical environment is similar to finger blanching as reported in the ISO 5349-1 document. The dose–response relationship of HAVS in a tropical environment is valid for finger tingling and numbness. Hence, we proposed to include the dose–response relationship information for neurological symptoms in the ISO 5349-1 document to facilitate its application in tropical environment.